Targeting hypoxia-induced tumor stemness by activating pathogen-induced stem cell niche defense - Bhuyan, Seema; Pal, Bidisha; Pathak, Lekhika; Saikia, Partha Jyoti; Mitra, Shirsajit; Gayan, Sukanya; Mokhtari, Reza Bayat; Li, Hong; Ramana, Chilakamarti V.; Baishya, Debabrat; Das, Bikul (Frontiers in Immunology, 2022)
Cancer stem cells (CSCs) reside in their tumor microenvironment (TME) niches, which are often hypoxic. Previously, we found that hypoxia and oxidative stress prevalent in TME may re-program CSCs to a highly aggressive and inflammatory phenotype, the tumor stemness switch (TSS) phenotype.We previously reported a “stem cell niche defense” mechanism in bone marro-wand lung mesenchymal stem cell niche against pathogen. Pathogen induced bystander apoptosis (PIBA) of stem cells harboring intracellular pathogen may be part of this defense mechanism. We speculate that the TSS phenotype may also activate this niche defense mechanism to defend their TME niche against pathogen and therefore could be exploited to target CSCs. Here we report that CSCs of TSS phenotype enriched in post-hypoxia ABCG2+ CSCs of several cell lines of diverse tumors including oral squamous cell carcinoma cell line SCC-25 exhibited bystander apoptosis when infected with either Bacillus Calmette Guerin (BCG) or mutant Mycobacterium tuberculosis (Mtb)strain 18b. The conditioned media (CM) of the infected cells not only exhibited marked anti-tumor activity in vivo, but also showed significant anti-microbial activity. A detailed mechanisms study revealed that some of the infected ABCG2+CSCs underwent pyroptosis and released a high mobility group box protein 1 (HMGB1)/p53 death signal that can induce a toll like receptor (TLR) 2/4 mediated bystander apoptosis. Thus, our findings suggest that PIBA can be utilized to activate the “niche defense” mechanism in TSS phenotype, which not only target the TSS, but also exhibit marked anti-tumor activity in vivo.